2011
DOI: 10.1111/j.1365-2796.2011.02418.x
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand factor predicts major bleeding and mortality during oral anticoagulant treatment

Abstract: Aims. Oral anticoagulation (OAC), predominantly with warfarin, is an effective treatment to prevent thromboembolic events. Serious bleeding is a frequent and feared treatment complication. In this longitudinal cohort study of OAC-treated patients, we aimed to evaluate the relationship between von Willebrand factor (VWF) levels and risk of bleeding complications, cardiovascular mortality and all-cause mortality.Methods and results. A total of 719 patients receiving warfarin treatment were observed for a mean du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This result sets VWF activation factor apart from VWF antigen, which has been associated with bleeding complications as well as cardiovascular events [10]. It was also noted that in patients with high levels of VWF activation factor and antigen, the incidences of cardiovascular events and mortality were especially high, indicating that these patients are at a highest risk.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This result sets VWF activation factor apart from VWF antigen, which has been associated with bleeding complications as well as cardiovascular events [10]. It was also noted that in patients with high levels of VWF activation factor and antigen, the incidences of cardiovascular events and mortality were especially high, indicating that these patients are at a highest risk.…”
Section: Discussionmentioning
confidence: 90%
“…The study cohort was recruited from the OAC clinic at Skellefteå County Hospital, Skellefteå, Sweden, in June 1996 and has in part been described in an earlier paper [10] Patients with a planned treatment time greater than 3 months were considered to be on long term treatment and eligible for the study; thus, consent forms were sent to them. Blood samples were obtained at inclusion for the 356 patients included in the final study cohort.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Paradoxically, high levels of vWF antigen are associated with both thrombotic events and bleeding complications in patients treated with OACs. 8,26 The mechanism for the dual association is not clear, and different pathways could contribute to high levels of vWF. It is also possible that vWF could be an effector in thrombotic events, possibly by increased binding to platelets.…”
Section: Discussionmentioning
confidence: 99%
“…However, several risk factors in these schemes are also associated with a higher risk of serious bleeding events [12][13][14]. In previous studies, we have shown that biomarkers in blood plasma are associated with bleeding complications during anticoagulant treatment, as well as with thromboembolic events [15]. To our knowledge the relationships between homocysteine and folate and risk of cardiovascular events or bleedings have not previously been investigated in patients with oral anticoagulant treatment.…”
Section: Introductionmentioning
confidence: 97%